The Moderating Effect of Narcissistic CEOs on Firm Profitability and Value - Vincent Christopher Nawing (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the effect of profitability on firm value and the moderating role of CEO narcissism. The research utilizes 225 financial reports from LQ45 companies, employing Moderated Regression Analysis (MRA) with the PROCESS application. Profitability is proxied by Return on Assets (ROA), firm value by Tobin's Q, and CEO narcissism by CEO photo analysis. The findings indicate that profitability has a positive and significant impact on firm value, aligning with signaling theory, which suggests that high profitability sends positive signals to investors. However, CEO narcissism weakens this relationship. Narcissistic CEOs tend to focus more on personal image and aggressive strategies, increasing information asymmetry and reducing investor trust. These results highlight that high profitability does not always enhance firm value when influenced by leadership that neglects long-term sustainability. Therefore, companies must consider governance aspects in CEO selection to maximize firm value in the long run.